Golf swing styles: A kinetic and 3D kinematic comparison - Neal, R.
wo styles of swinging are popular, the traditional left-to-right (LR) and the modern rotational (LB) style. The purpose of this research was to identify if either style was more consistent or generated higher club-head speed than the other.